RI 3299 Anhydrous Sodium Sulphate From Saline Deposits Or Brines By A Four-Stage Process (239170ee-57e1-4289-abab-7355805e2758) - J. E. Conley (The National Institute for Occupational Safety and Health (NIOSH), 1936)
[Available statistics show that the demands of the American chemical industry for sodium sulphate have been increasing slightly in recent years. The supply from domestic sources, particularly in the form of byproduct salt cake from the acid manufacturers, has been tending to decease due to the growing manufacture of synthetic acid. Both hydrochloric and nitric acids are being synthesized from their elements. The natural result has been that a smaller amount of salt cake is available. Simultaneously, the expansion of the Kraft-paper industry, especially in Lie South, has brought about greater demand for sodium sulphate in that section. This demand is being met by domestic byproduct salt cake, by imported German sodium sulphate made from potash waste liquors, and by favorably situated domestic deposits of Glauber salts and tile anhydrous salt, thenardite. No shortage of natural sodium sulphate exists in the United States, but usually such deposits occur in semiarid regions far re¬moved from transportation facilities and from markets. Moreover, the major portion of the natural deposits is Glauber salt or mirabilite (Na2SO4?10H20), which must be dried or dehydrated in order to most consumer requirements. The waters of hydration represents, roughly, 55 percent of tae total weight of the crude salts and therefore has a very important influence on transportation costs. In marry instances the cost of getting even the dehydrated product to market is the deciding economic factor. Therefore, the recovery or production of anhydrous sodium sulphate from plant-waste liquors or from natural brines of suitable composition might be economically feasible.]